Culinary herbs and spices in Nepal: A review of their traditional uses, chemical constituents, and pharmacological activities - Khanal, Asmita; Devkota, Hari Prasad; Kaundinnyayana, Sammodavardhana; Gyawali, Prakash; Ananda, Ravindra; Adhikari, Rameshwar (Ethnobotany Research and Applications, 2021)
Background: Herbs and spices have long been used for both food and medicinal purposes in different world civilizations. In Nepal, various herbs and spices are used for culinary purposes. In addition, a range of bioactive compounds present in herbs and spices have been associated with multiple beneficial health properties. This paper aims to illustrate the diverse availability of traditional herbs and spices used in Nepali cuisine with their traditional uses along with their major phytochemicals and pharmacological activities. Methods: Information related to traditional uses, chemical constituents and pharmacological activities were compiled from the published research articles, books, and book chapters. Results: This study documented 50 herbs and spices with their traditional uses, the phytochemicals present and their medicinal application. Numerous bioactive compounds are reported such as polyphenols, quinines, organosulfur compounds, flavonoids, alkaloids, polypeptides, etc. and these compounds possess diverse pharmacological activities. These herbs and spices were primarily studied for their antimicrobial, anti-inflammatory, antioxidant, antidiabetic, antihyperlipidemic, hepatoprotective, and antipyretic activities. Conclusion: The different scientific studies highlighted in this review suggest that most of the health effects of herbs and spices are observed on various chronic diseases, including cancer, cardiovascular diseases and diabetes. The antioxidant and anti-inflammatory properties of culinary herbs and spices can act to improve the overall health system. There are nutraceutical potentials that may open new opportunities for herb and spices-based enterprises. Keywords: Spices, herbs, culinary, phytochemicals, medicine, health benefits